Analysis of alternative splicing with microarrays: successes and challenges - Lee, Christopher (BioMed Central, 2004)
Recently, DNA microarrays have emerged as potentially powerful tools for analyzing alternative splicing. We briefly review the latest results in this field and highlight the current challenges that they have revealed.